Development of the Al-Ḥuzn wa Al-Jazā’ Identification Instrument Based on the Thoughts of Abu Zayd al-Balkhī: Pengembangan Instrumen Identifikasi Al-Ḥuzn wa Al-Jazā’ Berdasarkan Pemikiran Abu Zayd al-Balkhī - Tuhfi Fitria Abdullah; Putri Anditasari; Cucu Setiawan; Andi Juwita Amal; Dodo Wirdada; Firman Rismanto (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2026)
This study aims to construct and explore the dimensional structure of the al-ḥuzn wa al-jazā’ identification instrument, grounded in the classical psychosomatic framework of Abu Zayd al-Balkhī. The primary focus is to map emotional indicators that facilitate a preventive-proactive approach to mental health assessment. Utilizing an exploratory quantitative design, data were analyzed through Exploratory Factor Analysis (EFA), yielding a robust KMO value of 0.882. The findings led to the reduction of the instrument from 76 to 49 items, which settled into four distinct factors: Psychological Distress, Cognitive Resilience, Emotional-Physiological Stability, and Behavioral regulation. While the results confirm the hypothesized four-dimensional structure, a substantive shift was observed: cognitive, affective, behavioral, and physical aspects underwent an integrative fusion into a single primary distress factor, whereas adaptive dimensions emerged independently due to the item direction effect. These implications contribute to a more holistic multidimensional measurement model, though the efficacy of reverse-scored items warrants further validation through Confirmatory Factor Analysis (CFA). The originality of this research lies in its successful transformation of 9th-century psychosomatic terminology into a modern psychometric structure that captures an individual’s adaptive assets alongside clinical symptoms.